Clinical and histopathological profile of patients with multiple myeloma and renal involvement (Journal of Renal and Hepatic Disorders, 2025)
Background: Multiple Myeloma (MM) is a malignant disorder of plasma cell characterised by the clonal expansion of aberrant plasma cells within the bone marrow. This leads to the excessive production of monoclonal immunoglobulins (M-protein) and associated with organ dysfunction. Renal disease is a frequent and a potentially significant complication of multiple myeloma. The range of renal lesions observed in the patients with multiple myeloma is diverse. The aim of present study is to find the clinical and histopathological profile of patients with multiple myeloma and renal involvement and their clinico-pathological correlation. Methods: This was an observational hospital based study where 33 patients with multiple myeloma as well as renal involvement who agreed for renal biopsy were included. Demographic data, mode of presentation and need for dialysis were noted. Appropriate laboratory tests and radiological survey were done. Results: The median age of the patients in our study was 56 years. Fatigue was the most common clinical feature. The indications for renal biopsy were acute kidney injury (AKI), chronic/progressive reduction in glomerular filtration rate (GFR) with normal sized kidneys and nephrotic syndrome. Histopathological findings in the patients with acute kidney injury included myeloma cast nephropathy, acute tubulointerstitial nephropathy, acute tubular necrosis and IgA (Immunoglobulin A) nephropathy. In cases with chronic decline in GFR, observed lesions were myeloma cast nephropathy, monoclonal immunoglobulin deposition disease, membranoproliferative glomerulonephritis, chronic interstitial nephropathy and diabetic nephropathy. For patients presenting with nephrotic syndrome, amyloidosis and monoclonal immunoglobulin deposition disease were predominant. Conclusions: Renal involvement is considered as one of the main feature of multiple myeloma and is often the initial manifestation of the disease. Renal biopsy is crucial for establishing a specific diagnosis and providing valuable prognostic and therapeutic insights.
Keywords: Acute kidney injury; Amyloidosis; Chronic kidney disease; Multiple myeloma; Myeloma cast nephropathy